Spectral Characterization, Thermal and Antimicrobial Studies of Some Divalent Metal Chelates of 7-((3-Phenyl-4,5-dihydroisoxazol-5-yl)methyl)quinolin-8-ol - A. Alothman, Asma; D. Albaqami, Munirah; A. Alshgari, Razan (Asian Journal of Chemistry, 2020)
A series of Cu(II), Ni(II) and Co(II) azo chelates (AZC1-AZC3) of 7-((3-phenyl-4,5-dihydroisoxazol-5-yl)methyl)quinolin-8-ol have been designed and obtained. Thermal measurements, molar conductance, magnetic moment, elemental analyses, spectral (IR, UV-Vis, 1H and 13C NMR, ESR, mass) were used to characterize insulated solid complexes. The metal complexes were assumed to be non-electrolytic by molar conductance values. Thermal properties and decomposition kinetics of the metal chelates are investigated using Coats-Redfern method. The kinetic parameters like activation energy (E*), pre-exponential factor (A) and entropy of activation (ΔS*) were quantified. Results of spectral studies of mass and TGA data confirmed the octahedral geometry for all chelates. Finally, the synthesized metal-complexes were tested for their in vitro antimicrobial efficacy.